La emoción de la alegría en los Escolios a los salmos de Evagrio Póntico - Peretó-Rivas, Rubén (Vox Patrum, 2023)
In this paper I propose to analyse Evagrius Ponticus’ treatment of emotions, especially happiness, in his Scholia to the Psalms. First, I will contextualise Evagrius’ work, which has just been published, with its own characteristics, both in terms of literary genre and in terms of the type of Evagrian exegesis. Then, the place of emotions in the text will be discussed, with particular emphasis on happiness, on the basis of the analysis of all the occurrences of that concept in the Scholia. As a result, it is observed that Evagrius’ hermeneutic of the Psalms, at least in the case of happiness, is fundamentally allegorical, which would make impossible the existence of happiness in man in its classical sense, since it could only be experienced as the reaction to the possession of a spiritual good, which is gnosis or knowledge of God. In this way, the Scholia to the Psalms support the spiritualistic interpretation of Evagrius’ doctrine.